Case report and narrative review of the literature: a rare colonic stent failure in a palliative patient - Bressington, Morgan; O’Connor, Alexander; Telford, Karen (Frontiers in Gastroenterology, 2023)
INTRODUCTION: With palliative patients, a holistic approach is important. Interventions should minimise hospital length of stay, maximise quality of life, and control symptoms. A self-expanding metal stent (SEMS) for the palliative treatment of malignant large bowel obstruction (MLBO) is designed to provide these benefits to patients approaching the end of their life. We present the case of a patient treated with a SEMS over two years earlier for MLBO. He was treated with palliative intent at diagnosis because his frailty and medical comorbidities precluded surgery. He later presented with severe tenesmus, and these new symptoms were later found to be due to a rare stent failure where the stent had fractured and was irretrievable. This had to be managed conservatively before the patient sadly passed away seven months later. DISCUSSION: A SEMS is considered the first line treatment to relieve MLBO caused by an inoperable left sided colonic cancer. This treatment offers reduced length of stay, reduced stoma rates, fewer complications, and comparable survival compared to de-functioning stoma. However, SEMS are not expected to be in use for extended periods of time. The literature reports an average survival after a colonic stent insertion of between 121 and 199 days when used in a palliative setting.CONCLUSION: This is one of the first case reports to describe a colonic stent failure occurring over two years after insertion. This case argues that further research into the longer-term outcomes of this management option is warranted, particularly as palliative patients are living longer.